2015
DOI: 10.4049/jimmunol.1403225
|View full text |Cite
|
Sign up to set email alerts
|

Tr1 Cells, but Not Foxp3+ Regulatory T Cells, Suppress NLRP3 Inflammasome Activation via an IL-10–Dependent Mechanism

Abstract: The two best-characterized types of CD4+ regulatory T cells (Tregs) are Foxp3+ Tregs and Foxp3− type 1 regulatory (Tr1) cells. The ability of Foxp3+ Tregs and Tr1 cells to suppress adaptive immune responses is well known, but how these cells regulate innate immunity is less defined. We discovered that CD44hiFoxp3− T cells from unmanipulated mice are enriched in Tr1 cell precursors, enabling differentiation of cells that express IL-10, as well as Tr1-associated cell surface markers, CD49b and LAG-3, and transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 44 publications
5
95
0
Order By: Relevance
“…FoxP3 + Tregs can also be cytotoxic (55), however ThCTL are FoxP3 negative. Type 1 regulatory cells lack FoxP3 expression as well, however these cells often express high levels of Lag-3 (56, 57), which ThCTL are low for at the peak of the infection. The lack of transcription factors associated with the other major CD4 subsets, suggests that few if any of the ThCTL have differentiated down other polarized cytokine pathways including those expressed by Th2 (GATA-3 expressing), T FH (Bcl6-expressing), Th17 (RORγt) or FoxP3 + Treg.…”
Section: Resultsmentioning
confidence: 99%
“…FoxP3 + Tregs can also be cytotoxic (55), however ThCTL are FoxP3 negative. Type 1 regulatory cells lack FoxP3 expression as well, however these cells often express high levels of Lag-3 (56, 57), which ThCTL are low for at the peak of the infection. The lack of transcription factors associated with the other major CD4 subsets, suggests that few if any of the ThCTL have differentiated down other polarized cytokine pathways including those expressed by Th2 (GATA-3 expressing), T FH (Bcl6-expressing), Th17 (RORγt) or FoxP3 + Treg.…”
Section: Resultsmentioning
confidence: 99%
“…This is shown in studies of mice with abnormalities of IL-10 production or signaling, where IL-10 has been shown to have a profound inhibitory effect on NLRP3 inflammasome activity; therefore, the absence of IL-10 leads to increased IL-1β production (27). In these studies, it has been shown that IL-10-KO and IL-10R-KO mice exhibit increased NLRP3 inflammasome activity and that an NLRP3 inflammasome inhibitor, such as glyburide or caspase-1 inhibitor, ameliorates colitis occurring in such mice (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome activation is required for protective immune responses against certain pathogens and participates in a wide array of disease processes, including ischemia reperfusion injury with relevance to transplantation. Previously published work has additionally shown that complement activation and insertion of the MAC into myeloid cells triggers inflammasome activation, delineating an interactive crosstalk mechanism between these 2 innate immune systems 8 .…”
mentioning
confidence: 97%